Efek Mediasi Motivasi Kerja Pada Pengaruh Budaya Organisasi Terhadap Kinerja - Irsal Fauzi (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study is to determine the effect of organizational culture on performance. The motivation variable becomes the intervening variable. The approach in this study uses quantitative methods. The analysis technique used linear regression test and pathway analysis as a mediation test. The results showed that organizational culture had a significant effect on performance and motivation was able to mediate the influence of organizational culture on performance. This research can provide information to management in managing human resources, meaning that managing human resources is inseparable from factors that can affect its performance. In principle, the purpose of managing human resources is to achieve mutual prosperity between the company and all employees involved with company activities.